2012
DOI: 10.1159/000338620
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Merkel Cell Polyomavirus in the Human Tissues from 41 Japanese Autopsy Cases Using Polymerase Chain Reaction

Abstract: It has recently been shown that approximately 80% of Merkel cell carcinomas harbor a novel polyomavirus named Merkel cell polyomavirus (MCPyV). MCPyV has been detected in human tissue samples. However, detailed distribution of MCPyV in non-neoplastic Japanese human tissues remains unclear. To address this, we used single or real-time quantitative polymerase chain reaction (PCR) for 41 autopsy cases. PCR revealed MCPyV-DNA in non-neoplastic samples: total, 29/41 (71%); adult, 29/39 (74%); fetus or infant, 0/2; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Oral cavity samples had 0.026 copies/genome, while MCCs had an average of 10 copies/genome (range, 173-0.05 copies̸genome) and saliva had an average of 0.128 copies/genome (range, 5-0.01) (7). Matsushita et al (17) did not detect MCPyV DNA in non-neoplastic tissues from 10 tongue samples and 2 salivary gland samples from FFPE sections of autopsy cases. The MCPyV prevalence in the present study was 7.0% (23/327).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Oral cavity samples had 0.026 copies/genome, while MCCs had an average of 10 copies/genome (range, 173-0.05 copies̸genome) and saliva had an average of 0.128 copies/genome (range, 5-0.01) (7). Matsushita et al (17) did not detect MCPyV DNA in non-neoplastic tissues from 10 tongue samples and 2 salivary gland samples from FFPE sections of autopsy cases. The MCPyV prevalence in the present study was 7.0% (23/327).…”
Section: Discussionmentioning
confidence: 96%
“…Using quantitative polymerase chain reaction (qPCR), MCPyV has been detected in malignant and benign tumours (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Moreover, certain investigators have reported that low viral loads of MCPyV have also been detected in normal human tissue samples, including skin, liver and respiratory secretions, suggesting that this virus is widespread in the human body (7,17). However, previous studies on the frequency of MCPyV infection in oral tumours or tumour-like lesions are partial and incomplete (7,15).…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type MCPyV may reside in skin and other tissues, with a high prevalence of infection in the general population (15,26,27). MCPyV-associated MCC is thought to arise in the rare event when MCPyV aberrantly integrates into the genome of the tumor progenitor cell and undergoes truncation or mutation of the LTAg gene that renders the virus replication-deficient but transformation-competent (2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, qPCR does not allow for direct correlation with tissue morphology, hence preventing confirmation of adequate tumor content and localization of signal to tumor cells. This is relevant because qPCR may detect the presence of wild-type MCPyV in various tissues (27), and reliable cutoffs have not been demonstrated for distinguishing background MCPyV infection from tumor MCPyV. Hence, there is potential for false positive results by qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The MCPyV viral load on the skin surface varies from less than 1 copy per 1000 cells to 1000 copies per cell (9,26,30,(39)(40)(41). The mean DNA copy per cell in normal skin has been reported to be 0.02-0.07 (42).…”
Section: Detection Of the Viral Genomementioning
confidence: 99%